2012
DOI: 10.1186/1743-7075-9-58
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of neonatal exposure to monosodium glutamate and aspartame on glucose homeostasis

Abstract: BackgroundRecent evidence suggests that the effects of certain food additives may be synergistic or additive. Aspartame (ASP) and Monosodium Glutamate (MSG) are ubiquitous food additives with a common moiety: both contain acidic amino acids which can act as neurotransmitters, interacting with NMDA receptors concentrated in areas of the Central Nervous System regulating energy expenditure and conservation. MSG has been shown to promote a neuroendocrine dysfunction when large quantities are administered to mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 63 publications
2
60
0
Order By: Relevance
“…An increment in the body weight, transitory increases in the blood pressure and in plasma values of glucose and triglycerides alongside a transitory reduction in plasma urea was also reported after aspartame consumption [8]. Alteration of Glucose homeostasis by aspartame ingestion was also well documented a decade before [25]. Aspartame had the capacity to alter the normal antioxidant enzyme pool in many organs like liver and kidney [30].…”
Section: Possible Associated Health Concernsmentioning
confidence: 91%
See 2 more Smart Citations
“…An increment in the body weight, transitory increases in the blood pressure and in plasma values of glucose and triglycerides alongside a transitory reduction in plasma urea was also reported after aspartame consumption [8]. Alteration of Glucose homeostasis by aspartame ingestion was also well documented a decade before [25]. Aspartame had the capacity to alter the normal antioxidant enzyme pool in many organs like liver and kidney [30].…”
Section: Possible Associated Health Concernsmentioning
confidence: 91%
“…Reduction in mean placental and maternal-fetal weights, in umbilical cord length and kariometric parameters in fetal hepatocyte nuclei majority of kariometric parameters of the hepatocytes were also well documented after aspartame treatment in rats [6]. In utero exposure of aspartame may affect spatial cognition and glucose homeostasis in mice, particularly in males [25]. An increment in the body weight, transitory increases in the blood pressure and in plasma values of glucose and triglycerides alongside a transitory reduction in plasma urea was also reported after aspartame consumption [8].…”
Section: Possible Associated Health Concernsmentioning
confidence: 94%
See 1 more Smart Citation
“…It was observed that males were more susceptible than females in many cases. [25][26][27][28] High level of the naturally occurring essential amino acid phenylalanine is a health hazard to those born with phenylketonuria (PKU) a rare inherited disease. So the patients of phenylketonuria should not consume aspartame.…”
Section: Possible Associated Health Concernsmentioning
confidence: 99%
“…6 In utero exposure of aspartame may affect spatial cognition and glucose homeostasis in mice, particularly in males. 25 An increment in the body weight, transitory increases in the blood pressure and in plasma values of glucose and triglycerides alongside a transitory reduction in plasma urea was also reported after aspartame consumption.…”
mentioning
confidence: 99%